Investigating the Potential Effects of Implementation of Value Added Tax in Iran - Sedaghat Galeshkalami , Iman; Jabbari, Hasan; Panahian , Hossein; Arabzadeh , Maryam; Mazroui Nasrabadi , Esmaeil (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
The present study has investigated the possible effects of the implementation of value added tax on Iran's inflation in companies listed on the Tehran Stock Exchange. The temporal domain of this information is related to the financial statements of the manufacturing companies accepted in the Tehran Stock Exchange in the period of 6 years from the beginning of 2013 to the end of 2018. The obtained data includes manufacturing and service companies and institutions. And there are no other than leasing companies and financial institutions, insurance and banks, and their obtained information has been uploaded based on the Kodal site. To check the liquidity growth, its base year has been obtained from 2013. In this chapter, the collected data have been evaluated in two sections of descriptive and inferential statistics; In the descriptive analysis of information, the indicators of descriptive statistics include frequency, percentage of relative frequency, mean, standard deviation, and in the inferential part, research hypotheses have been investigated using independent variables on the dependent variable. In the following, efforts were made to investigate the direct and indirect effects of statistical equations and Eviews10, Excel software. The results showed that there is a direct relationship between value added tax and gross national product, liquidity growth, the amount of money in circulation, the amount of tax revenues and finally inflation in Iran.